The peculiarities of establishing the charter air transportation: European experience in Ukraine - Tetyana Prymak; Liubov Ivchenko; Nataliia Pohuda; Valentyna Levchenko; Viktor Trynchuk (Innovative Marketing)
This paper highlights the problems associated with the poor quality of services and the lack of effective marketing interaction between all the participants of the charter air transportation in the tourist summer season of 2018 in Ukraine. The paper aims to develop an algorithm for the actions of all participants of tourist services market in order to establish effective marketing interaction based on the analysis of the reasons influencing the destabilization of the tourist services market in the field of charter air transportation. Flight delay statistics were selected for June-July 2018 due to the fact that it was during this period that the problem manifested itself especially sharply. So, not time-series data, but cross-sectional data were selected for the analysis of the problem cause. At the same time, for confident conclusions about the increase in passenger traffic, 5-year periods were chosen, namely, the period 2014–2018 was compared with the period 2009–2013. During the research, statistical methods of one-factor linear correlation-regression analysis were used, as well as a comparative analysis of the indicators of the charter air transportation participants’ performance in Ukraine. The analysis of charter air transportation market showed that increasing the age of the aircraft in a year leads to a decrease in the proportion of timely flights by 2.5%. The marketing analysis proves that the rapid increase in the number of passengers was caused by the explosive increase in irregular flights. The results of the study also indicate that the well-organized interaction between the tour operator and the airlines significantly affects the timeliness of the flights. Based on defined problems of the charter air transportation market, a set of recommendations has been proposed for improving the marketing interaction of all market participants: tourists, tour operators, airlines and government agencies.